Conjugated Quantum Dots Inhibit the Amyloid β (1-42) Fibrillation Process - GIORDANI, SILVIA; ZHANG, HONGZHOU; MOVIA, DANIA (My University, 2011)
Nanoparticles have enormous potential in diagnostic and therapeutic studies. We have demonstarted that the amyloid beta mixed with and conjugated to dihydrolipoic acid (DHLA)-capped CdSe/ZnS quantum dots (QDs) of size approximately 2.5 nm can be used to reduce the fibrillation process. Transmission 2 electron microscopy (TEM) and atomic force microscopy (AFM) were used as tools for analysis of fibrillation. There is a significant change in morphology of fibrils when amyloid ? (1-42) (A? (1-42)) is mixed or conjugated to the QDs. The length and the width of the fibrils vary under modified conditions. Thioflavin T (ThT) fluorescence supports the decrease in fibril formation in presence of DHLA-capped QDs.
PUBLISHED
Keywords: Particles and fields physics; Nanoparticles; Nanoscience & Materials; Neuroscience